It's Hurricane Season Do You Know Where Your Storm Is?. - Gall, R. (IEEE spectrum)
Weather forecasting accuracy is expected to further improve with the continuing developments in computer and satellite technologies as well as advances in the scientific understanding of how weather evolves. Within the next 10 years, the two- to three-day hurricane forecast will be as accurate as the generally spot-on 24-hour forecast is today. Even more important, from the viewpoint of emergency officials, the four- to six-day forecast will give solid and reliable information on which to base evacuation orders. Not only will fatalities and false alarms be avoided, billions of dollars will also be saved each year